Creating Hierarchical Topographies on Fibrous Platforms Using Femtosecond Laser Ablation for Directing Myoblasts Behavior - Jun, Indong; Chung, Yong-Woo; Heo, Yun-Hoe; Han, Hyung-Seop; Park, Jimin; Jeong, Hongsoo; Lee, Hyunjung; Lee, Yu Bin; Kim, Yu-Chan; Seok, Hyun-Kwang; Shin, Heungsoo; Jeon, Hojeong (American Chemical Society, 2016)
Developing an artificial extracellular matrix that closely mimics the native tissue microenvironment is important for use as both a cell culture platform for controlling cell fate and an in vitro model system for investigating the role of the cellular microenvironment. Electrospinning, one of the methods for fabricating structures that mimic the native ECM, is a promising technique for creating fibrous platforms. It is well-known that align or randomly distributed electrospun fibers provide cellular contact guidance in a single pattern. However, native tissues have hierarchical structures, i.e., topographies on the micro- and nanoscales, rather than a single structure. Thus, we fabricated randomly distributed nanofibrous (720 +/- 80 nm in diameter) platforms via a conventional electrospinning process, and then we generated microscale grooves using a femtosecond laser ablation process to develop engineered fibrous platforms with patterned hierarchical topographies. The engineered fibrous platforms can regulate cellular adhesive morphology, proliferation, and distinct distribution of focal adhesion proteins. Furthermore, confluent myoblasts cultured on the engineered fibrous platforms revealed that the direction of myotube assembly can be controlled. These results indicate that our engineered fibrous platforms may be useful tools in investigating the roles of nano- and microscale topographies in the communication between cells and ECM.